Boron-Doped Pine-Cone Carbon With 3D Interconnected Porosity for Use as an Anode for Potassium-Ion Batteries With Long Life Cycle - Lu, Jian-Fang; Li, Ke-Chun; Lv, Xiao-Yan; Kuai, Hong-Xiang; Su, Jing; Wen, Yan-Xuan (Frontiers in Chemistry, 2022)
Potassium-ion batteries (KIBs) have received widespread attention as an alternative to lithium-ion batteries because of their low cost and abundance of potassium. However, the poor kinetic performance and severe volume changes during charging/discharging due to the large radius of potassium leading to low capacity and rapid decay. Therefore, development of anode materials with sufficient space and active sites for potassium ion deintercalation and desorption is necessary to ensure structural stability and good electrochemical activity. This study prepared boron-doped pine-cone carbon (BZPC) with 3D interconnected hierarchical porous in ZnCl2 molten-salt by calcination under high temperature. The hierarchical porous structure promoted the penetration of the electrolyte, improved charge-carrier diffusion, alleviated volume changes during cycling, and increased the number of micropores available for adsorbing potassium ions. In addition, due to B doping, the BZPC material possessed abundant defects and active centers, and a wide interlayer distance, which enhanced the adsorption of K ions and promoted their intercalation and diffusion. When used as the anode of a KIB, BZPC provided a high reversible capacity (223.8 mAh g−1 at 50 mA g−1), excellent rate performance, and cycling stability (115.9 mAh g−1 after 2000 cycles at 1 A g−1).